HYBRID NO-LOSS IMAGE COMPRESSION ALGORITHM BASED ON DISCRETE WAVELET TRANSFORMATION WITH ADAPTIVE PREDICTION - A. A. Boriskevich; L. A. Ruiz (Informatika)
A hybrid no-loss compression algorithm is proposed. It is based on a new local adaptive lifting discrete wavelet transformation, which provides higher accurate approximation of smooth, edge and texture image areas and minimization of side information on adaptation, and on a tree-block wavelet structures that control the trade-off between the speed and compression ratios. The simulation results of the proposed algorithm show that its compression efficiency is superior to standard JPEG2000 algorithm for test gray scale images France, Mandrill, Barbara and Lena on 6, 10, 8 and 8 %, respectively.